Facilitating Professional Skills Through Student Engagement Activities for the Holistic Development of the Learner - Kona, Preethi; Tadimalla, Sri Yeswanth (Journal of Engineering Education Transformations, 2025)
This paper focuses on the professional skills required to transform the student in to a successful individual and competent professional. Graduates entering today’s workplace face many challenges, especially how to learn and function in unfamiliar and unpredictable situations. Multi-skilled, multinational project teams, requiring collaboration, cooperation, flexibility and inter-cultural awareness, demand high levels of professional and interpersonal skills. Graduates must be able to service their own administrative needs and are routinely required to work longer hours than their predecessors. The professional skills should be gained over a period of time with self-learning and experience. Though many institutions have been conducting several activities to develop the professional skills in the students, the outcomes are not so effective and the gap is still noticeable. It should be a practice to the students through which they gain a lot of experience. To address this issue, several initiatives and activities are identified to make the students involve themselves and various professional skills needed for the student in their journey are depicted in the table.